Characteristics of phosphorus sorption kinetics on sediments at different initial phosphorus concentrations - HUANG Li-dong; CHAI Ru-shan; ZONG Xiao-bo; ZHANG Yong-song (浙江大学学报. 农业与生命科学版)
Two different sediments (Meiliangwan and Huajiachi) were selected to study the effect of initial P concentration (C0) on P sorption kinetics and to identify the corresponding sorption kinetic type. Kinetics studies were carried out using an agitated batch method. The kinetics of sorption were followed based on the amounts of P adsorbed at various time intervals. The data were analyzed using pseudo-first order and pseudo-second order equations. The results showed that: 1) for the Meiliangwan sediment, the process belonged to a two-stage dynamic: an initial fast exchange of P followed by a much slower process, and its sorption quantity was much larger than that of the Huajiachi sediment, which could be seen as chemical sorption. For the Huajiachi sediment, the sorption process was slow and had a small absorbing capacity, which belonged to physical sorption, and the data points fluctuated greatly; 2) the zero equilibrium P concentration (EPC0) in the Meiliangwan and Huajiachi sediments was 0.03 and 0.42 mg·L-1, respectively. When C0 < EPC0, the sediment desorbed P, or else the sediment adsorbed P; 3) the sorption data in the Meiliangwan and Huajiachi sediment followed pseudo-second order and pseudo-first order kinetic model respectively by investigating the theoretical criteria and comparing standard residual error and correlation coefficient; 4) the sorption quantity and sorption rate of sediments increased with increasing C0. Besides, the higher the C0 value was, the longer time was required to achieve equilibrium. From the relationship between C0 and kinetic parameters, generalized predictive models for P adsorbed onto sediments at any contact time and initial P concentration within the given range were proposed. These equations could then be used to derive the amount of P adsorbed at any given ion concentration and the reaction time. It will be helpful to understand the P transfer differences between sediments.